ANALYSIS OF INFORMATION SERVICES FOR TEACHERS AND STUDENTS DENGAN MODEL Delone and McLean - Andi Arfian; Dede Mustomi; Herryansyah h; Syafrianto sy; Juarni Siregar (Technologia : Jurnal Ilmiah, 2022)
In the era of globalization. Improving information for teachers and students is one of the must and one of the requirements in facing the rapid development of digital information, especially services, especially in school environments such as teachers and students, absolutely carried out by the school to improve the quality and useful information services. This researcher analyzes the quality of service for teachers and students at SMKN5 Bekasi City whether the services have been properly implemented and in accordance with the initial goal of establishing a school website system, namely making the center and improving information services, In this analysis using the DeLone and McLean model for teachers and students. in managing the analysis using the Sem PLS method with SmartPls tools in data management. research, measuring the quality of a website based on the de lone mc lean instrument, namely system quality, information quality, service quality, usage, level of satisfaction and benefits. which is positive and significant for all variables, namely system quality, service quality, information quality, user satisfaction level and net benefits and service quality have no effect on user satisfaction and from the research results it is found that the Smkn 5 Bekasi City Website service is successful and in accordance with the information provided. used by teachers and students. Keywords: SemPls,  Delone Mclean ,SmartPls